Root exudates influence rhizosphere fungi and thereby synergistically regulate Panax ginseng yield and quality - Sun, Jin; Yang, Jing; Zhao, Shuyue; Yu, Qian; Weng, Lili; Xiao, Chunping (Frontiers in Microbiology, 2023)
Root exudates contain a complex array of primary and specialized metabolites that play important roles in plant growth due to their stimulatory and inhibitory activities that can select for specific microbes. In this study, we investigated the effects of different root exudate concentrations on the growth of ginseng (Panax ginseng C. A. Mey), ginsenoside levels, and soil fungal community composition and diversity. The results showed that low root exudate concentrations in the soil promoted ginseng rhizome biomass and ginsenoside levels (Rg1, Re, Rf, Rg2, Rb1, Ro, Rc, Rb2, Rb3, and Rd) in rhizomes. However, the rhizome biomass and ginsenoside levels gradually decreased with further increases in the root exudate concentration. ITS sequencing showed that low root exudate concentrations in the soil hardly altered the rhizosphere fungal community structure. High root exudate concentrations altered the structure, involving microecological imbalance, with reduced abundances of potentially beneficial fungi (such as Mortierella) and increased abundances of potentially pathogenic fungi (such as Fusarium). Correlation analysis showed that rhizome biomass and ginsenoside levels were significantly positively correlated with the abundances of potentially beneficial fungi, while the opposite was true for potentially pathogenic fungi. Overall, low root exudate concentrations promote the growth and development of ginseng; high root exudate concentrations lead to an imbalance in the rhizosphere fungal community of ginseng and reduce the plant’s adaptability. This may be an important factor in the reduced ginseng yield and quality and soil sickness when ginseng is grown continuously.